Dynamic evaluation of job search assistance - Stephen Kastoryano; Bas van der Klaauw (Institute for the Study of Labor (IZA), 2011)
This paper evaluates a job search assistance program for unemployment insurance recipients. The assignment to the program is dynamic. We provide a discussion on dynamic treatment effects and identification conditions. In the empirical analyses we use administrative data from a unique institutional environment. This allows us to compare different microeconometric evaluation estimators. All estimators find that the job search assistance program reduces the exit to work, in particular when provided early during the spell of unemployment. Furthermore, continuous-time (timing-of-events and regression discontinuity) methods are more robust than discrete-time (propensity score and regression discontinuity) methods.
urn:nbn:de:101:1-201104084350
Keywords: C22; J64; J68; 330; treatment evaluation; dynamic enrollment; empirical evaluation; Arbeitsmarktpolitik; Arbeitsvermittlung; Arbeitsuche; Wirkungsanalyse; Berufliche Integration; Schätzung; Niederlande